Avian Influenza H9N2 Seroprevalence among Poultry Workers in Pune, India, 2010 - Pawar, Shailesh D.; Tandale, Babasaheb V.; Raut, Chandrashekhar G.; Parkhi, Saurabh S.; Barde, Tanaji D.; Gurav, Yogesh K.; Kode, Sadhana S.; Mishra, Akhilesh C. (PloS one, 2012)
Avian influenza (AI) H9N2 has been reported from poultry in India. A seroepidemiological study was undertaken among poultry workers to understand the prevalence of antibodies against AI H9N2 in Pune, Maharashtra, India. A total of 338 poultry workers were sampled. Serum samples were tested for presence of antibodies against AI H9N2 virus by hemagglutination inhibition (HI) and microneutralization (MN) assays. A total of 249 baseline sera from general population from Pune were tested for antibodies against AI H9N2 and were negative by HI assay using ≥40 cut-off antibody titre. Overall 21 subjects (21/338 = 6.2%) were positive for antibodies against AI H9N2 by either HI or MN assays using ≥40 cut-off antibody titre. A total of 4.7% and 3.8% poultry workers were positive for antibodies against AI H9N2 by HI and MN assay respectively using 40 as cut-off antibody titre. This is the first report of seroprevalence of antibodies against AI H9N2 among poultry workers in India.